PIK3CA, KI67, Estrogen (ER) and Progesterone Receptors (PR) Expression Pattern of in HER2 Positive Breast Cancers - Ogenyi, Samuel I.; Onu, June A.; Ibeh, Nancy C.; Madukwe, Jonathan U.; Onu, Onyekachi A.; Menkiti, Felix E. (Asian Pacific Journal of Cancer Biology, 2022)
Background: PIK3CA mutations have been reported to be associated with resistance to therapy in HER2+ breast cancers. This study, therefore, became imperative to determine the expression pattern of this mutant protein together with ER, PR and KI67 in order to serve as a useful predictive tool in the management of HER2 breast cancers. Methods: A total of 53 archived formalin-fixed, paraffin-embedded HER2+ breast cancer tissue blocks from 2015 to 2019 were used for the study in NAUTH Nnewi. The selected blocks were sectioned and stained with haematoxylin and eosin staining techniques. HER2, ER and PR status confirmation as well as PIK3CA and KI67 protein expressions were evaluated using immunohistochemistry (Avidin-biotin complex method). PIK3CA and KI67 expressions in the tissue were scored based on proportion and intensity of immune-labelling using the semi-quantitative method. Result: The mean age of subjects was 47 years and the breast cancers were all invasive ductal carcinoma. Twenty-nine (54.7%) were ER+ while 24 (45.3%) were ER-. Twenty-one (39.6%) were PR+ while 32 (60.4%) were PR-. Twenty-one (39.6%) were PIK3CA negative, 9(35.8%) showed low PIK3CA, while 13(24.5%) showed high PIK3CA. Thirty-four (64.2%) were negative for KI67, 11(20.8%) showed low KI67, while 8(15.5%) showed high KI67. There was weak and moderate positive relationship between ER/PR status and PIK3CA (r=-0.032; p=0.822) and KI67 (r=0.050; p=0.721) respectively. A weak negative correlation between KI67 and PIK3CA (r=-0.118; p=0.401) were observed with 12 (22.4%) of the 13 highly positive PIK3CA cases showing either negative or low for KI67 immunoreactivity while 7(13.2%) of the 8 highly positive KI67 cases showed either negative or low PIK3CA immunoreactivity. Conclusion: This study established a moderate expression of PIK3CA mutant protein. It also pointed out an existing interesting relationship between PIK3CA and KI67, which can be further revealed in future studies.